2021
DOI: 10.2196/19194
|View full text |Cite
|
Sign up to set email alerts
|

A Mobile App to Support Clinical Diagnosis of Upper Respiratory Problems (eHealthResp): Co-Design Approach

Abstract: Background The misuse of antibiotics is a global public health issue that fosters bacterial resistance and jeopardizes generational health. The development of validated tools such as web-based courses and mobile apps to enhance clinical decisions in upper respiratory infections is of great importance in reducing the incorrect use of antibiotics in these situations. Objective The aim of this study was to design and prevalidate the interface of a mobile a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…In the study of Karthikeyan et al, (2019) a total of 475 applications related to eye care were identified on the Android platform, yet ophthalmologists participated in the design and development of only 107 (22.53%) applications [ 39 ]. The design of clinical systems according to the opinion of users with different backgrounds helps to interpret and use the systems more easily and consequently enhance them [ 40 , 41 ]; it is therefore recommended to use the opinions of both technical and clinical experts in designing these systems more fully from technical and clinical perspective.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Karthikeyan et al, (2019) a total of 475 applications related to eye care were identified on the Android platform, yet ophthalmologists participated in the design and development of only 107 (22.53%) applications [ 39 ]. The design of clinical systems according to the opinion of users with different backgrounds helps to interpret and use the systems more easily and consequently enhance them [ 40 , 41 ]; it is therefore recommended to use the opinions of both technical and clinical experts in designing these systems more fully from technical and clinical perspective.…”
Section: Discussionmentioning
confidence: 99%
“…The eHealthResp mobile app is an e-health tool developed to assist primary care physicians in advising patients in cases of respiratory tract disorders (see Supplementary Material S2 ). It includes a physician profile composed of five algorithms based on the suspected disease: (i) acute otitis media, (ii) acute rhinosinusitis, (iii) acute pharyngotonsillitis, (iv) acute tracheobronchitis, and (v) community-acquired pneumonia, and guides the most likely diagnosis and potential therapeutic approaches, based on respiratory symptoms [ 23 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Both the courses and the mobile application have been previously validated by experts in relation to their contents (including the clinical cases) by using the Delphi Method approach [ 22 ], as well as for their usability, through usability testing [ 23 , 24 ], thus highlighting its user-friendliness, consistency, and usefulness.…”
Section: Methodsmentioning
confidence: 99%
“…Evidence suggests that mobile phone apps can facilitate medication adherence by using functions such as reminder alerts and providing access to drug information [11]. Furthermore, many mobile apps to support health care professionals during their practice have been developed [12][13][14], thus promoting personalized and efficient health care. Therefore, the potential of MEDs, including laptops, tablets, and especially mobile phones, related to facilitating activation to navigate health information on the web is expected to be highly advantageous to not only patients but also health professionals.…”
Section: Introductionmentioning
confidence: 99%